Акустическая камера для диагностики насосных агрегатов; Научно-технический вестник ОАО "НК "РОСНЕФТЬ"; № 1 - Рыбаков Е. А. Евгений Александрович; Стариков Д. П. Дмитрий Павлович; Зебзеев А. Г. Алексей Григорьевич; Громаков Е. И. Евгений Иванович (2016, 2016)
Заглавие с экрана